The role of amino acids in albumin synthesis and catabolism - Kelman, Leslie (Department of Medicine, 2020)
Modern concepts of the structure, function and metabolism of proteins have evolved painstakingly through the centuries. In September, 1772, Rutherford discovered the gas which was later named nitrogen by Chaptal in 1790 . The fundamental importance of nitrogen in the body was only appreciated after Gay-Lussac and Thenard had pioneered chemical procedures for organic analysis. Magendie applied this knowledge to dietary constituents and concluded that nitrogen was an essential component of the diet. His early insight into metabolism was depicted in his view that body constituents are continuously being replaced, the rate being dependent on the tissue. In 1838 the term"protein" was coined by Gerard Mulder for substances containing a basic nitrogenous component.